Influence of Irradiation on Electronic Transition of (CuO) Films Prepared by Chemical Spray Paralysis Technique - Fakralden, D. J.; Hamed, S. A.; Abdul-Allah, M. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this  research,  We  study the effect  of  irradiation  by  gamma rays from (Cs137) source  for the period time (21) days on optical propertices such as absorption coeffeicient (ï¡)and  energy gap (Eg) for  copper oxides thin films (CuO) prepared by the chemical spray pyrolysis and deposited on glass substrates at (350oC) for two different thicknesses  (  1000Ã…and 3000Ã…) .